ANALISIS MINAT MASYARAKAT MUSLIM MENJADI NASABAH BANK SYARIAH (STUDI KASUS DI GAMPONG PONDOK KEMUNING) - febi febi; Muhammad Dayyan; Fahriansah Fahriansah; Juprianto Juprianto (JIM: Jurnal Ilmiah Mahasiswa, 2019)
The development of sharia banking in Indonesia is currently progressing. This is evidenced by the number of Conventional Banks that started to open the Sharia Business Unit. However, the development of the Sharia Bank has not been able to influence the interest of the community to become a customer of Sharia Bank. The condition occurred in Gampong Pondok Kemuning which all of the people are Moslems. However, people's interest in becoming a customer in Sharia Bank is still low. The purpose of this study is to determine the system of socialization conducted by Islamic banks in Gampong Pondok Kemuning and To know the interests of Muslim communities Gampong Pondok Kemuning to become customers in Islamic banks. This research uses qualitative approach. Research subjects are the people of Gampong Pondok Kemuning. The sample of this research is 10 people by using purposive sampling method. Data collection techniques used were interviews. The analytical method used is qualitative descriptive The results of the research show that socialization has not been done directly by the bank to the community in Gampong Pondok Kemuning, Approach and product offerings conducted by Bank Syariah is still lacking. The interest of the Gampong Pondok Kemuning community is caused by the socialization, product offerings, knowledge and income obtained by the community.